Stable heterocumulene monomer in water; Synthesis and polymerization of (meth)acrylates having an isothiocyanate structure. Issue 21 (31st July 2013) - Seto, Ryota; Matsumoto, Kozo; Endo, Takeshi
ABSTRACT Novel methacrylate and acrylate monomers having an isothiocyanate structure, 2‐isothiocyanatoethyl methacrylate (ITEMA) and 2‐isothiocyanatoethyl acrylate (ITEA), were synthesized, and their radical polymerizations were examined, respectively. ITEMA and ITEA were synthesized by addition of carbon disulfide to 2‐aminoethyl methacryrate or 2‐aminoethyl acrylate, followed by treatment with ethyl chloroformate. Radical polymerizations of the obtained monomers (ITEMA, ITEA) were carried out methyl ethyl ketone using 2, 2'‐azobisisobutyronitrile (AIBN) as an initiator to obtain the corresponding polymers. The glass transition temperatures of the poly‐ITEMA and poly‐ITEA were determined to be 55 and 2 °C by differential scanning calorimetry, respectively. The 5 wt % decomposition temperatures of the poly‐ITEMA and poly‐ITEA were determined to be 277 and 269 °C by thermogravimetric analysis, respectively. Isothiocyanato groups in the monomers did not react with water in acetone solution at 60 °C for 24 h to be tolerable to water. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4522–4529